Wetlands Alliance Program implementation phase - Gonsalves, Julian Francis (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2013)
WorldFish is working with partners in the Mekong Region to support a new alliance of regional and local partners that will contribute towards sustainable wetlands management that benefit the poor. This project supports the Wetlands Alliance, an extensive network of organizations—government, civil and NGOs—actively engaged in developing innovative solutions to poverty alleviation. The Alliance helps local partners to build the capacity they need to work effectively with communities that they are supporting. With backstopping support from experienced regional partners, local partners work with communities to identify key issues and jointly develop appropriate initiatives.